Comparison of Clinical and Laboratory Features in RT-PCR Positive and RT-PCR Negative Covid-19 Patients Admitted in High Dependency Unit in a Tertiary Care Hospital, SGRH, Lahore - Khadija Muneer, Saima Ayub, Nauman Zafar, Noma Sarwar, Adnan Hasham, Shazia Siddique (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Corona virus disease 2019 (COVID-19) is currently diagnosed mainly using reverse transcriptase polymerase chain reaction (RT-PCR). Yet a significant proportion of patients have negative RT-PCR result. A comparative study of RT-PCR negative patients with RT-PCR positive patients will help understand clinical characteristic and differences of this diseased population. Objective: To compare the clinical and laboratory features of RT-PCR Positive and RT-PCR negative patients admitted in high dependency unit. Patients and methods: In this retrospective cohort study, the data of 128 patients (59 patients with RT-PCR positive result and 69 patients with RT-PCR negative results) was obtained. These patients had been admitted in high dependency unit of a community hospital. Demographics, clinical characteristics and laboratory abnormalities were noted and a comparison was done using statistical analysis. Results: In our study-total 128 patients were enrolled out of which 68 (53.1%) were males and 60 (46.9%) were females. 59 (46.1%) patients were RT-PCR positive and 69 (53.9%) patients were RT-PCR negative. Median age was 55.34 years (18 to 95). No significant difference was noted in most of clinical symptoms (fever, sputum production, rhinorrhea, dyspnea, myalgia, nasal congestion, vomiting, diarrhea, urinary symptoms, altered level of consciousness), comorbidities (diabetes mellitus, hypertension, prior lung disease, prior ischemic heart disease, prior kidney disease), laboratory abnormalities (elevated creatinine, elevated liver enzymes, elevated ferritin, elevated C-reactive protein, elevated d-dimers, elevated procalcitonin, abnormal electrocardiogram). Cough was significantly found to be more prevalent in RT-PCR positive patients (p=0.042) and severe disease was also more prevalent in these patients significantly (p=0.000). Conclusion: Our study shows that patients admitted and diagnosed to be suffering from COVID-19 infection had remarkable similarities in clinical features and laboratory parameters regardless of RT-PCR status, however RT-PCR positive patients suffered from more severe pneumonia as compared to RT-PCR negative patients.